Manajemen Kesiswaan di SDIT (Sekolah Dasar Islam Terpadu) Harapan Mulia Palembang - Yuri Dullah; Munir Munir (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
The purpose of this articleis to answer the formulation problem which includes planning, organizing, implementing and controlling. This research used a descriptive approach that explains the characteristics of existing problems. The subjects of this study consisted of the principal, vice principal of curriculum, vice principal of student, head of administration staff and school's operator. Data collection techniques used are guidelines for observation, interview, and documentation. Data analysis used the Miles and Huberman model techniques, namely 1) Data reduction, 2) Data Presentation, and 3) Drawing Conclusions or Data Verification.The results of this study are as follows: 1) Planning, starting from analyzing the needs of students by considering the number of classes and teachersavailable, conducting student's activities, selecting students, the school orientation period and recording of new student data. 2) Organizing, including the division of students who are divided based on low, medium, and high competencies. Classroom management is carried out by the homeroom teacher which includes classroom management, student attendance, class set up, making a picket list, lesson schedule, arranging student seating, making class plans, and filling out report cards. 3) Implementation, starting from student's discipline, services in school library, canteen, school health treatment, transportation, intracurricular and extracurricular activities. 4) Supervision, consist of some activities to assess the student learning process, graduation and alumni seach.